The relationship of perceived value, service quality, brand trust, and brand loyalty : a literature review - Ikramuddin; Muhammad Adam; Hizir Sofyan; Faisal (Expert journal of marketing, 2017)
The concept of loyalty has evolved as an important issue in the world of marketing as companies are focusing their strategy in retaining customers and increasing their sales. The purpose of this study is to re-evaluate the involvement of various factors related to the perception of value, service quality, brand trust and brand loyalty in the industry of mobile phones through literature review and examination of previous research. Some studies have found that the observed variables are the key drivers of brand loyalty. However, other opinions are also presented for their different perspectives and a broader view of the research topic.
2758454-9; 2344-6773; Expert journal of marketing; 778946770